Parkinson's Disease: Clinical Signs and Symptoms, Neural Mechanisms, Positron Emission Tomography, and Therapeutic Interventions - K. L. Leenders; W. H. Oertel (Neural Plasticity)
Parkinson's disease is one of the most frequent neurodegenerative brain diseases. Its time course is slow and is characterized by progressive loss of dopaminergic and other brainstem neurons resulting in malfunctioning of the cerebral neuronal systems responsible for motor functions. The clinical signs are slowness of movement, muscle rigidity and rest-tremor amongst other features. The cause of the disease is unknown, but recently involvement of genetic factors is being researched. Positron emission tomography (PET) allows in vivo determination of striatai dopaminergic activity. This has increased our insight in the pathophysiology of the disease and permits direct study of disease progression at a biochemical level and equally to monitor whether potential neuroprotective interventions are indeed effective. Thus far no drug has emerged but promising substances are currently being studied.